Collective Action and Education on Instagram against Online Gender-Based Violence in Indonesia - Andina, Tri Kurnia Revul (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study aims to investigate how education and collective action on Instagram have contributed to helping the public understand the urgency of eliminating online gender-based violence (OGBV) in Indonesia. Instagram accounts that have been examined include @taskforce_kbgo, @srikandikbgo, and @stop.kbgo. Those accounts were chosen because they primarily address OGBV, as the number of cases in Indonesia has kept increasing throughout the years. This study uses a qualitative descriptive approach encompassing online observation, interview, and documentation. Online observation is conducted to discover those accounts' communication patterns and activities. In addition, the researcher interviewed one of the actors behind to discover their motivations, their goals, and the processes in managing their advocacy. The findings show that those accounts focus on educating the public about OGBV and its rising cases in Indonesia. By promoting this issue, they can raise awareness of OGBV and minimize the risks of using digital platforms. Furthermore, they have created content that can captivate young people since they are active and prominent users of digital platforms. Digital platforms, including social media, have made collective action possible beyond time and space. These works have allowed the public to be well-informed and well-equipped with skills and knowledge on OGBV.